Efektivitas Hukum Sistem Online Single Submission Risk-based Approach (OSS-RBA) Terhadap Pertumbuhan Pelaku Umkm Di Kota Medan - Harahap, Nurasiah; Lestari, Dina (Universitas Islam Sumatera Utara, 2023)
The economic development approach is proposed to people's economic actors, especially cooperatives and SMEs. Development aimed at cooperatives and MSMEs is expected to lead to a more coherent and balanced arrangement of the structure of national economic actors so that a strong and independent structure of national economic actors develops. Thus, Cooperatives and SMEs are the heart of the people's economy and the pioneers of the growth of people's economy.This study uses normative and empirical legal research, with a statutory approach (Statue Approach) and a case approach (Case Approach) and a conceptual approach (Conceptual Approach).Based on research data, the level of MSME actors who obtained the issuance of a Business Identification Number (NIB) based on risk-based business licensing through the OSS-RBA system, was very low, namely from the number of 26,150 MSMEs in 2021 who obtained NIB with MSME actors who had migrated under Government Regulations. Number 5 of 2021 in Articles 562 and 563 which came into force at the Investment Agency and One Door Integrated Services (DPMPTSP) in Medan City starting on August 4, 2021, until June 15, 2022, there were only around 693 MSME actors. So that the implementation of the Government Regulation has not been effective in the growth of MSME actors in Medan,This reality is inseparable from the obstacles in the growth of MSME actors in Medan, both internal constraints, regarding Human Resources at the Medan DPMPTSP who still do not understand and external constraints, related to awareness and legal culture of MSME actors, as well as new regulations. enforced. Finally, it is hoped that the Department of Cooperatives and the Medan DPMPTSP must continuously facilitate and provide socialization and technical guidance, as well as Assistance services for Filling Business Licensing to MSME Actors while for Human Resources in the Medan City DPMPTSP, must conduct training and comparative studies so that they can increase the growth of SMEs. Keywords: Legal Effectiveness, Risk-Based Approach OSS System (OSS-RBA) System, Micro, Small and Medium Enterprises (MSMEs), Medan City.